STRATEGI NAFKAH BURUH NELAYAN KERAMBA JARING APUNG DI WADUK JATILUHUR (Solidarity: Journal of Education, Society and Culture, 2014)
This research studying about livelihood strategies of Keramba Jaring Apung (KJA) fishing workers in Jatiluhur Lake. This Research use approach qualitative with research location in District of Jatiluhur, Purwakarta Regency, West Java. Subject research were KJA fishing workers in Jatiluhur Lake. Technique data collecting use interview, observation, and documentation. Technique to test authenticity of data use data triangulation. Result of research indicate that KJA fishing workers are people who contribute energy to work to skipper of KJA with salary. Their job is to plant seeds of fish, spread or fish feeding, maintaining a pool, check on cages, crossing services, as well as being energy harvesting and porters. Every day fishing workers stay in hut that built around the cages and can return home in accordance with the agreed time with skipper. Livelihood strategies of KJA fishing workers is diversification of livelihoods, patron-client relationships, and intensification/extensification. Livelihood strategies of KJA fishing workers is influenced by factors supporting and inhibiting factors, namely natural capital, economic capital, human capital, and social capital.